2013
DOI: 10.1136/bmjqs-2013-002341
|View full text |Cite
|
Sign up to set email alerts
|

Interactive questioning in critical care during handovers: a transcript analysis of communication behaviours by physicians, nurses and nurse practitioners

Abstract: Differences across clinician type and levels of clinical training were found in both measures during patient handovers. The findings suggest that training could enable physicians and nurses to learn communication competencies during patient handovers which were used more frequently by more experienced practitioners, including interjecting less frequently and using interactive questioning strategies to clarify understanding, and assertively question the appropriateness of diagnoses, treatment plans and prognose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 30 publications
3
54
0
4
Order By: Relevance
“…In the same issue [30] concluded that nursing students performed significantly better when providing and receiving handoff after they gain handoff knowledge in training program. Additionally, [33] has described the positive effect of handoff training in handoff receiver skills. Without handoff education, the nursing students lacked awareness of the importance of an active handoff recipient in creating a shared mental model.…”
Section: Discussionmentioning
confidence: 99%
“…In the same issue [30] concluded that nursing students performed significantly better when providing and receiving handoff after they gain handoff knowledge in training program. Additionally, [33] has described the positive effect of handoff training in handoff receiver skills. Without handoff education, the nursing students lacked awareness of the importance of an active handoff recipient in creating a shared mental model.…”
Section: Discussionmentioning
confidence: 99%
“…Resident physicians participating in patient handofs may not interact regularly with each other, may be located in diferent parts of the healthcare systems, may have diferent skill and experience levels, or may come from diferent clinical backgrounds [3]. Adherence to hierarchical norms between junior and senior residents or atendings can further exacerbate relational communication barriers relecting diferences across levels of training or between clinician types in the willingness to engage in interactive questioning strategies to assertively challenge erroneous assumptions and actions during a handover with peers [7,17]. Entrenchment of handof routines in departmental or hospital mores may require transformational change of an institution's culture in order to improve them [19].…”
Section: Barriers To Efective Handofsmentioning
confidence: 99%
“…More than merely the passive transfer of information, optimum handofs necessitate the eicient communication of information among participants [3]. Expansion of duty hour restrictions for resident physician trainees in North America have increased handof frequency, augmented the potential for inefectual handof-induced complications, and stimulated the need for new interventions to improve handover quality [7]. The shift from the traditional model of continuous inpatient medicine to a team-based model has further focused atention on patient handofs [3].…”
Section: Transitions Of Care: Handof Deinitionmentioning
confidence: 99%
See 2 more Smart Citations